1981
DOI: 10.2307/2442715
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Observations on the Early Imbibition of Water by Sida spinosa (Malvaceae) Seed

Abstract: The chalazal area is confirmed as the site of initial water entry into prickly sida (Sida spinosa L.) seeds. Very early during imbibition of water, a kidney-shaped area of the seed coat separates from underlying cells forming a blister. This blister may also be induced in dry seeds (both afterripened and nonafterripened) when pressure is applied to the chalazal area. Blisters form more readily on afterripened seeds than on nonafterripened seeds, however, and the event is correlated with an increase in seed coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0
8

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 13 publications
(26 reference statements)
4
27
0
8
Order By: Relevance
“…of the families with PY, except the Leguminosae, occurs only after a plug or lid that closes the discontinuity ('water-gap') in the waterimpermeable layer(s) in the chalazal region is dislodged or disrupted, thereby creating a pore for entrance of water to the embryo. In Malvaceae, the so-called chalazal plug separates from the underlying subpalisade layer (Egley & Paul 1981;Egley et al 1986;Egley 1989), and in Cannaceae the imbibition lid separates from the rupture layer (Grootjen & Bouman 1988). The subpalisade layer and the rupture layer occur only below the chalazal plug and imbibition lid, respectively, in seeds in these two families.…”
Section: Cochlospermaceaementioning
confidence: 99%
“…of the families with PY, except the Leguminosae, occurs only after a plug or lid that closes the discontinuity ('water-gap') in the waterimpermeable layer(s) in the chalazal region is dislodged or disrupted, thereby creating a pore for entrance of water to the embryo. In Malvaceae, the so-called chalazal plug separates from the underlying subpalisade layer (Egley & Paul 1981;Egley et al 1986;Egley 1989), and in Cannaceae the imbibition lid separates from the rupture layer (Grootjen & Bouman 1988). The subpalisade layer and the rupture layer occur only below the chalazal plug and imbibition lid, respectively, in seeds in these two families.…”
Section: Cochlospermaceaementioning
confidence: 99%
“…In Malvaceae the raphal tissue releases from the seed and exposes the chalazal area with a median cleft. Only raising of a blister, containing a region of the palisade layer, induces imbibition and germination (EGLEY & PAUL 1981). The seed dormancy in legume seeds is usually considered to be effected through the physical restriction of water uptake by the impermeable outer part of the epidermal layer of the Malpighian cells (WERKER 1980/1981, TRAN & CAVANAGH 1984, GOPINATHAN ~5 BABU 1985, SERRATO-VALENTI & al.…”
Section: Discussionmentioning
confidence: 99%
“…The chalazal area of prickly sida seeds was earlier confirmed as the site of initial water entry into the imbibing seed (Egley and Paul, 1981). It was also reported that a kidney-shaped portion of the seed coat near the chalazal slit formed a blister just prior to onset of imbibition in nonhard seeds.…”
mentioning
confidence: 83%
“…SEED COAT IMPERMEABILITY to water is an important factor in the dormancy and longevity of many weed seeds in the soil (Lewis, 1973;Stoller and Wax, 1974;Rolston 1978;Egley and Chandler, 1978). These seeds, often described as "hard," may survive for several years during which time the coats of some become permeable resulting in imbibition of water and germination.…”
mentioning
confidence: 99%
See 1 more Smart Citation